Effect of pulsed electric field on yield and absorption of Basil essential oil - Baghdad, Abdelkader; Elkebir, Abdelkader; Miloudi, Kaddour; Kherbouche, Fouad; Benmimoun, Youcef; Hamimed, Abderrahmane (Journal of Agriculture and Applied Biology, 2025)
The effect of applying pulsed electric field (PEF) treatments on Basil leaves for essential oil extraction was studied. After treatment with pulsed electric field (PEF) with an intensity of 2 kV.cm-1, specific energy of 5kJ.kg-1 and 60 min of distillation, the yield of Basil EO increased from 0.63% (Control) to 0.82%, an increase of 30.16%. However, when basil leaves were treated with very high specific energy PEF (50 kJ.kg-1) a non-significant increase in EO yield compared to the control was observed. This experimental study reports the results regarding the effect of pulsed electric field (PEF) treatment on the absorbance of Basil EO. The study allowed us to recognize an increase in EO absorption by the application of PEF with moderate specific energies. This has significance in quality control, which is an essential factor for the use of essential oils in various applications.